Screening on the influenced parameters in asiaticoside extraction from Centella asiatica by two-level factorial design - Ruslan, Fatin Shazwani; Farhani, Afiqah; Mohamed Mustafa, Qamellia; Darnis, Deny Susanti; Bakhtiar, M. Taher (AIP Publishing, 2022)
Centella asiatica has been widely exploited in the cosmeceutical and pharmaceutical industries due to its biological properties, owing to the presence of asiaticoside. This study applied Soxhlet extraction method in extracting asiaticoside since this conventional method is easy to handle and acts as a reference method for new advanced methods. Also, the objective of this study is to determine the influence of the independent parameters namely, sample: solvent, solvent: co-solvent ratios, and extraction time to the yield of asiaticoside content. The effects of three independent parameters were analysed using Two-Level Factorial Design. The significance of the model was analysed using ANOVA analysis, which studied at p-value < 0.05. From Two-Level Factorial Design, the individual parameters namely sample: solvent, solvent: co-solvent ratios, and extraction time were insignificant to the asiaticoside content (p > 0.05). However, the interaction between factors; sample: solvent and solvent: co-solvent ratios exhibited a significant effect (p < 0.05) to the asiaticoside content. The optimal extraction condition suggested by Two-level Factorial were 1: 50, 100 %, and 7 hours for sample: solvent ratio, solvent, and extraction time, respectively. Hence, the suggested extraction conditions can be further applied in future research to extract asiaticoside from C. asiatica using Soxhlet extraction method.